2022
DOI: 10.1038/s41380-022-01551-5
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the brain erythropoietin circle to explain adaptive brain hardware upgrade and improved performance

Abstract: PrefaceExecutive functions, learning, attention, and processing speed are imperative facets of cognitive performance, affected in neuropsychiatric disorders. In clinical studies on different patient groups, recombinant human (rh) erythropoietin (EPO) lastingly improved higher cognition and reduced brain matter loss. Correspondingly, rhEPO treatment of young rodents or EPO receptor (EPOR) overexpression in pyramidal neurons caused remarkable and enduring cognitive improvement, together with enhanced hippocampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 107 publications
2
20
0
Order By: Relevance
“…The relative abundance was calculated by determining the observed fraction of each cell-type compared to the expected fraction and using a two-sided Fisher exact test to identify cell-types that were significantly enriched in EPO samples. Stars denote the p-values that have been adjusted using the Bonferroni correction (p<0.05= *, p<0.01= **, p<2.2e -16 = ***).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative abundance was calculated by determining the observed fraction of each cell-type compared to the expected fraction and using a two-sided Fisher exact test to identify cell-types that were significantly enriched in EPO samples. Stars denote the p-values that have been adjusted using the Bonferroni correction (p<0.05= *, p<0.01= **, p<2.2e -16 = ***).…”
Section: Resultsmentioning
confidence: 99%
“…One of the major adaptive responses to hypoxia involves hypoxia-inducible factors (HIF), which bind and transcriptionally activate their responsive elements embedded in the erythropoietin (EPO) gene [11][12][13] . In essence, the endogenous EPO system in the brain provides valuable fuel for individuals to renovate their synaptic and neuronal infrastructures upon facing metabolic challenges 2,[14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythropoietin (EPO) is a glycoprotein growth factor with an approximate molecular weight of 30.4 kDa firstly described in 1953 by Allan J Erslev as a specific kidney hormone stimulating the production of red blood cells [ 1 , 2 ]. Therefore, patients with anemia-related diseases like chronic kidney disease, viral infections and leukemia, are commonly treated with EPO [ 3 , 4 ]. Bunn and colleagues showed that regulation of EPO is based on low oxygen level (hypoxia) promoting the expression of hypoxia inducible factors (HIFs) and leading to increased production and secretion of EPO [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…All this is imitated by rhEPO treatment and contributes to cognitive improvement. Remarkably, the brain EPO circle can be entered anywhere, starting either with mild to moderate inspiratory hypoxia, with rhEPO treatment or with the aforementioned motor-cognitive challenge as inducer of functional hypoxia, leaving plenty of possible ways and also combinations thereof for future therapeutic interventions in neuropsychiatric diseases ( Ehrenreich et al, 2022 , Fernandez Garcia-Agudo et al, 2021 , Arinrad et al, 2021 , Wilke et al, 2021 , Wakhloo et al, 2020 , Butt et al, 2020 , Pan et al, 2019 , Hassouna et al, 2016 ).…”
mentioning
confidence: 99%